2022
DOI: 10.1021/acs.jpca.2c07150
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Near-Zero-Field Dephasing, Rephasing, and Relaxation Dynamics and [1-13C]Pyruvate Polarization Transfer Efficiency in Pulsed SABRE-SHEATH

Abstract: Hyperpolarized [1-13C]pyruvate is a revolutionary molecular probe enabling ultrafast metabolic MRI scans in 1 min. This technology is now under evaluation in over 30 clinical trials, which employ dissolution Dynamic Nuclear Polarization (d-DNP) to prepare a batch of the contrast agent; however, d-DNP technology is slow and expensive. The emerging SABRE-SHEATH hyperpolarization technique enables fast (under 1 min) and robust production of hyperpolarized [1-13C]pyruvate via simultaneous chemical exchange of para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 49 publications
0
31
0
2
Order By: Relevance
“…Accordingly, we used the J HC = 0.06 Hz value for the simulations, which is below the FWHM of the 13 C lines of 1- 13 C-pyruvate (see the Supporting Information for further details). This value is two orders of magnitude below the one used before to simulate the spin evolution of this system (5 Hz in ref ). Note, however, that if indeed the lifetime of complex τ Ir is about 31 ms as was estimated here (Figure ), then due to fast exchange, the lines will collapse in one and no J -coupling interactions below ∼1/τ Ir ∼ 30 Hz (and 1/ T 2 *) will be resolved (see the example in the Supporting Information, Figure S3).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Accordingly, we used the J HC = 0.06 Hz value for the simulations, which is below the FWHM of the 13 C lines of 1- 13 C-pyruvate (see the Supporting Information for further details). This value is two orders of magnitude below the one used before to simulate the spin evolution of this system (5 Hz in ref ). Note, however, that if indeed the lifetime of complex τ Ir is about 31 ms as was estimated here (Figure ), then due to fast exchange, the lines will collapse in one and no J -coupling interactions below ∼1/τ Ir ∼ 30 Hz (and 1/ T 2 *) will be resolved (see the example in the Supporting Information, Figure S3).…”
Section: Resultsmentioning
confidence: 72%
“…SABRE can also be used to hyperpolarize pyruvate and does not require hydrogenation. Instead, transient interactions with an Ir-complex are sufficient to hyperpolarize pyruvate without chemical modification, as depicted in Figure a. The polarization transfer from parahydrogen (pH 2 ) to pyruvate was demonstrated at ultralow magnetic fields below 1 μT, where the pH 2 -derived protons and the 13 C nucleus of pyruvate become strongly coupled and anticrossings of nuclear spin energy levels occur. This principle is used in the technique known as SABRE in shield enables alignment transfer to heteronuclei, SABRE-SHEATH. After hyperpolarization in SABRE-SHEATH experiments, the magnetic field is typically elevated to a few Tesla for detection.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the efficient hyperpolarization of KIC and [1- 13 C]KIC and demonstrated P 13 C levels of up to 18% with 13 C T 1 values of up to 74.1 ± 0.7 s. This high degree of polarization is enabled by favorable 13 C relaxation dynamics in microtesla magnetic fields. It is anticipated that P 13 C can be increased further through the use of a higher p-H 2 pressure [ 73 ] and flow rates using more advanced instrumentation. When using an NMR-tube-based experimental setup, a sufficiently high dose of HP contrast agent was produced for future in vivo studies, as demonstrated by pilot experiments in a freshly euthanized mouse.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, pulsed static fields have been used to induce this effect, delivering similar 13 C polarization (P13C) of HP [1- 13 C]pyruvate as SABRE-SHEATH. [18][19][20][21] Pulsed radiofrequency (rf) fields can be employed for polarization transfer. [22,23] Spin-lock induced crossing (SLIC) by continuous rf irradiation at tesla fields has 2 also been applied along with SABRE and was termed lowirradiation generation of high tesla-(LIGHT-) or SLIC-SABRE.…”
mentioning
confidence: 99%
“…These pyruvate polarization levels are two to six times higher than P13C values reported using SABRE before. [10][11][12][13]21] To better understand why SLIC-SABRE at µT fields shows such high efficacy, we carried out experiments using both 3 protonated and deuterated pyruvate and using SLIC-SABRE and SABRE-SHEATH. The 13 C polarization levels are shown in Fig.…”
mentioning
confidence: 99%